Sentinel Lymph Node Biopsy in Vulvar Cancer. Literature Review - К. V. Menshikov (Креативная хирургия и онкология)
Vulvar cancer is a fairly rare pathology. One of the factors in its aggressive course is the high metastatic potential of such tumors. The presence of metastases in inguinal lymph nodes constitutes a major prognostic factor. Starting from a 1-mm depth of invasion (FIGO IB), the risk of metastatic lymph node involvement increases to 35%, which makes lymph node examination important. Until 1990, inguinofemoral lymphadenectomy was performed, among other things, to assess the status of inguinal lymph nodes in vulvar cancer. Inguinofemoral lymphadenectomy constitutes a rather extensive operation that is accompanied by a large number of postoperative complications, both in the short- and long-term periods. A study on the role of sentinel lymph node biopsy was published in 2008. Van der Zee et al. provided important evidence that the sentinel lymph node concept can be safely applied in vulvar cancer patients. In the surgical treatment of vulvar cancer, it is essential to assess the sentinel lymph node status in order to reduce the extent of surgical intervention.